"We're Supposed to Be Asleep?" Vigilance, Paranoia, and the Alert Methamphetamine User. (24th September 2013) - McKenna, Stacey A.
Abstract: The stimulant "benefits" of amphetamine and its derivative, methamphetamine, have endured since the drugs first became popular nearly a century ago. The concepts of increasing energy for functional purposes related to work and productivity have been well studied. However, the broader idea of increased alertness, and what this means in the lives of users, has not yet been sufficiently examined. This article draws from ongoing research with active methamphetamine users to explore the perceived benefits, drawbacks, and meanings of remaining alert—awake and vigilant—while most of the world sleeps. The experiences of several users are situated in the contexts of sociostructural and mental health issues that shape cycles of use and meanings of addiction.